(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In recent years, numerous studies have been conducted to examine the cytokine profiles in patients with COVID-19, shedding light on the immune response and the role of cytokines in the pathogenesis of the disease. In this article, we will explore the findings from these studies, the commonly altered cytokines in COVID-19 patients, and the association of cytokine levels with disease severity and clinical outcomes.